Al-Jabiri’s Quranic Hermeneutics and Its Significance for Religious Education (KEMANUSIAAN The Asian Journal of Humanities, 2023)
The Quran is believed to have always been in dialogue with mankind throughout the ages. Accordingly, each Muslim generation is responsible for presenting new interpretations. Therefore, al-Jabiri offered a hermeneutic approach to interpreting Quranic verses and Islamic turâts (cultural heritage) to explore the meanings and significance of sacred and canonical texts. This study aims to analyse al-Jabiri’s Quranic hermeneutics, its application and its significance for religious education. Hence, the application of the holistic method in analysing al-Jabiri’s works is to construct main ideas and contextual meanings. According to al-Jabiri, the hermeneutic approach fulfils the interpretation’s demand for objectivity and continuity. The conceptual framework of sharia universality and the main purpose of sharia is used as a contextualisation paradigm for the interpretation of scripture, while the chronology of revelation is used as a basis for contextually aligned interpretation. His efforts to formulate the concept of human rights in the Quran are based on the application of his hermeneutic approach to verses that speak of human nature. Although it does not specifically discuss education, al-Jabiri’s hermeneutic approach is appreciated as a foundation for the development of religious education. Therefore, religious education is required to execute its role in humanisation and hominization.